Mortgage lending in the system of social policy of a state - Auyezkhanuly А.А.; Sabitova, N.M. (BUKETOV BUSINESS REVIEW, 2017)
The article analyzes the role mortgage lending in the system of social policy of a state. For countries in transition like Kazakhstan, the problem of improving the living conditions is primarily important as on time meeting of housing needs may help to overcome social instability. The research presents that a mortgage lending has its own place in the system of social programs of the government. The state operates with the help of state legislative and executive power and provides socio-economic, organizational and legal conditions that regulate, facilitate and monitor social doctrine in the housing sector. In this system banks contribute to the realization of social programs through their objectives by using own tasks in the mortgage market. The research is concentrated on Kazakhstan’s case where the housing problem is resolved through active state participation using different supporting mechanisms. It reveals that the main driver on the housing market in Kazakhstan is the government, which actively fosters sector development by accepting the Regional Development Program until 2020. The research shows that 48 % of all mortgages during 2014–2016 provided with help of state support. This explained by lower interest rates and down payment for a mortgage loan as well as better lending terms. The results of the research showed that in the current situation the population increasingly relies to state support in mortgage lending.